Dealing with attributes non-attendance in a discrete choice experiment on valuation of tourist facilities attribute in Kenyir Lake, Malaysia - W. Mohamad, Wan Norhidayah; Willis, Ken; Powe, Neil Adrian (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Accounting for ignored attributes, or attribute non-attendance (ANA), in discrete choice experiment (DCE) is believed to produce more reliable willingness to pay (WTP) estimates. However, there is evidence that respondents who claimed to have ignored some attributes may simply have assigned them lesser importance. To explore this issue in the context of tourism research, a new follow-up question is used to investigate whether the respondents have ignored certain attributes or just assigned the attribute as of lesser importance when responding. Three different mixed logit (MXL) models were estimated and compared. Results generally indicate that some respondents do indeed ignore certain attributes, and some of them put less emphasis on certain attributes when making decisions. Comparison of the different MXL models reveals different WTP estimates, suggesting the importance of considering an appropriate method to deal with ANA.